Arheološka najdišča Ptuja = Archaeological Sites of Ptuj Rabelčja vas = Rabelčja vas - Horvat, Jana (Opera Instituti Archaeologici Sloveniae, 2010)
The region of Ptuj lies on one of the central traffic axes within the broader margins of the Eastern Alps, and already in the distant past represented an important settlement centre. This monograph incorporates the knowledge hitherto gained abouth settlement history, from the Eneolithic to the Early Middle Ages in the eastern area of Ptuj, in Rabelčja vas. The emphasis is on the Roman Period, when the eastern district of the Roman town of Poetovio was beginning to spread here.Within the area of Rabelčja vas, which comprises nearly one-third of the Roman town of Poetovio, over a period of two centuries more than 160 discoveries and researches have taken place. During the past four decades, extensive rescue excavations have been carried out here, which have revealed numerous prehistorical remains, and also the eastern, crafts quarter of the ancient town, together with the main road and extensive burial sites.